Perspectives of providing population of Ukraine with horticultural products - Кондратенко, П. В.; Шевчук, Л. М. (Scientific Progress & Innovations, 2012)
The problem of balanced nutrition of Ukrainians, in particular, providing the human organism with the most important nutritive substances contained in fruits and berries has been examined. Distribution of the main fruit crops croppage concerning its usage, e.g. realization fresh and processed fruit has been carried out on the basis of the perspective programm of the horticulture development up to 2017. Taking into consideration the terms of the fruits and berries ripening and their possible storage period the monthly norms of their consuming by the person have been calculated as well as the provision of human organism with the vitamin C.